2021
DOI: 10.1177/15501477211015145
|View full text |Cite
|
Sign up to set email alerts
|

HackerRank: Identifying key hackers in underground forums

Abstract: With the rapid development of the Internet, cybersecurity situation is becoming more and more complex. At present, surface web and dark web contain numerous underground forums or markets, which play an important role in cybercrime ecosystem. Therefore, cybersecurity researchers usually focus on hacker-centered research on cybercrime, trying to find key hackers and extract credible cyber threat intelligence from them. The data scale of underground forums is tremendous and key hackers only represent a small frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…While Benjamin et al [6] reported the number of threads started as a predictor of expertise, recent literature in cybersecurity and dark forum analysis have failed to recognize the sequence of message publication as a crucial predictor. Among the closest to this finding, Huang et al [27] and Marin et al [36] found that discussions started by key hackers were relevant and enabled the identification of expert hackers. Our findings are similar to Mousavi et al [38], who reported the presence of an "order effect" in online healthcare communities, where the first answer in a forum post by an expert positively influenced subsequent answers for a particular question.…”
Section: Results From the Cyber-risk Mitigation Modulementioning
confidence: 91%
See 1 more Smart Citation
“…While Benjamin et al [6] reported the number of threads started as a predictor of expertise, recent literature in cybersecurity and dark forum analysis have failed to recognize the sequence of message publication as a crucial predictor. Among the closest to this finding, Huang et al [27] and Marin et al [36] found that discussions started by key hackers were relevant and enabled the identification of expert hackers. Our findings are similar to Mousavi et al [38], who reported the presence of an "order effect" in online healthcare communities, where the first answer in a forum post by an expert positively influenced subsequent answers for a particular question.…”
Section: Results From the Cyber-risk Mitigation Modulementioning
confidence: 91%
“…Their study was able to find key hackers on forums with no reputation scores or even a fragile reputation system. Finally, Huang et al [27] proposed…”
Section: Background Work On Hacker Forums and Dark-side Of Informatio...mentioning
confidence: 99%
“…SNA is extensively used to identify key actors in underground forums [17], [31], [32]. Our centrality metric approach is similar to Pete et al [33], who constructed undirected graphs of six underground forums based on 6 months of observation, computed network statistics, and analyzed the network structure.…”
Section: B Social Network Analysis Of Underground Forumsmentioning
confidence: 99%
“…It extracts features of cybersecurity terms and builds a security word recognition model based on bidirectional LSTM networks and random forest algorithms, providing early warning capabilities for cybersecurity events. Huang Cheng et al [4] combined LDA topic analysis and network topology, proposing the HackerRank algorithm that utilizes an improved PageRank algorithm to effectively identify hacker communities and key members within the communities. Addressing the limited research on cross-forum activities in hacker forum monitoring, Andrew J.…”
Section: Related Workmentioning
confidence: 99%
“…Finally, we concatenate the global and local representations to derive the output of the encoding as in (4).…”
Section: Figure 1 the S-arcnn Modelmentioning
confidence: 99%